Analysis of the Implementation of the Independent Curriculum by Pancasila Study Profile Strengthening Project Class IV SDN 2 Rantepao - Hakpantria Hakpantria; Mersilina L. Patintingan; Yusem Ba’ru (Edumaspul: Jurnal Pendidikan, 2024)
The of this research is to learn about and describe a project inteded for improving the profile of Pancasila Class IV SDN 2 Rantepao students. The subjects of this study were fourth-grade students and the teachers of SD Negeri 2 Rantepao. It is located at Dr. Ratulangi, Singki' Village street, Rantepao District, North Toraja Regency, South Sulawesi. This research approach is qualitative research that focuses on the use of data obtained on site. This type of research is descriptive research that aims to describe or provide an overview of the implementation of the independent curriculum through a Project to Strengthen the Profile of Pancasila Students in Class IV of SD Negeri 2 Rantepao. The data collection methods used were observation, interviews and documentation. The results of the investigation indicated that the implementation of the autonomous curriculum by strengthening the student profile of pancasila in Class IV SD State 2 Rantepao was successfully implemented. In school or outside the school, the students have successfully applied all the indicators of the profile of the students of Pancasila, namely, faithful, godly and noble, globally independent, confident, critical and creative. The P5 activities are carried out in a local context.